PELATIHAN PENGOLAHAN DATA MENGGUNAKAN APLIKASI SPSS UNTUK MENINGKATKAN KOMPETENSI MAHASISWA DALAM MENGANALISIS DATA - Irwandi; Nurafni Oktaviyah (Rafandha Press, 2022)
The obligation for every student at the end of his study period is research. Students are required to write research to obtain a bachelor's degree. The problem in the field is that most of them do not have experience in conducting research and do not know the right program that can be used to facilitate the process of processing data. Moreover, in operating the data processing program, most students are not capable. Therefore, training is needed for students that aims to provide knowledge and competence to process data using the application of a data processing program, namely Statistical Product and Service Solutions (SPSS) version 21. Training activities use lecture, practice, and discussion methods. This training was successful because there was an increase in students' ability to understand and master SPSS.